Pulmonary hypertension in patients with COPD: results from the comparative, prospective registry of newly initiated therapies for pulmonary hypertension (COMPERA) - Vizza, Carmine Dario; Hoeper, Marius M.; Huscher, Doerte; Pittrow, David; Benjamin, Nicola; Olsson, Karen Maria; Ghofrani, H. Ardeschir; Held, Matthias; Klose, Hans; Lange, Tobias; Rosenkranz, Stephan; Dumitrescu, Daniel; et al. (Chest, 2021)
Background - Pulmonary hypertension (PH) in COPD is a poorly investigated clinical condition. - Research Question - Which factors determine the outcome of PH in COPD? - Study Design and Methods - We analyzed the characteristics and outcome of patients enrolled in the Comparative, Prospective Registry of Newly Initiated Therapies for Pulmonary Hypertension (COMPERA) with moderate or severe PH in COPD as defined during the 6th PH World Symposium who received medical therapy for PH and compared them with patients with idiopathic pulmonary arterial hypertension (IPAH). - Results - The population included incident patients with moderate PH in COPD (n = 68), with severe PH in COPD (n = 307), and with IPAH (n = 489). Patients with PH in COPD were older, predominantly male, and treated mainly with phosphodiesterase-5 inhibitors. Despite similar hemodynamic impairment, patients with PH in COPD achieved a worse 6-min walking distance (6MWD) and showed a more advanced World Health Organization functional class (WHO FC). Transplant-free survival rates at 1, 3, and 5 years were higher in the IPAH group than in the PH in COPD group (IPAH: 94%, 75%, and 55% vs PH in COPD: 86%, 55%, and 38%; P = .004). Risk factors for poor outcomes in PH in COPD were male sex, low 6MWD, and high pulmonary vascular resistance (PVR). In patients with severe PH in COPD, improvements in 6MWD by ≥ 30 m or improvements in WHO FC after initiation of medical therapy were associated with better outcomes. - Interpretation - Patients with PH in COPD were functionally more impaired and had a poorer outcome than patients with IPAH. Predictors of death in the PH in COPD group were sex, 6MWD, and PVR. Our data raise the hypothesis that some patients with severe PH in COPD may benefit from PH treatment. Randomized controlled studies are necessary to explore this hypothesis further. - Trial Registry - ClinicalTrials.gov; No.: NCT01347216; URL: www.clinicaltrials.gov
Gesehen am 31.03.2022